Safety outcomes and long-term effectiveness of ex vivo autologous cultured limbal epithelial transplantation for limbal stem cell deficiency. Issue 5 (19th August 2016) - Fasolo, Adriano; Pedrotti, Emilio; Passilongo, Mattia; Marchini, Giorgio; Monterosso, Cristina; Zampini, Roberto; Bohm, Elisabetta; Birattari, Federica; Franch, Antonella; Barbaro, Vanessa; Bertolin, Marina; Breda, Claudia; et al.
Abstract : Purpose: To evaluate the safety and effectiveness of ex vivo autologous cultured limbal stem cell transplantation (CLET). Methods: We reviewed the clinical records of 59 consecutive patients treated with 65 CLETs. Efficacy was graded 1 year after surgery as successful, partially successful or failed. A safety analysis was performed considering side effects and complications that were recorded during the first year after CLET and those reported later than 1 year, including the events related to subsequent treatments. Results: The mean post-CLET follow-up was 6.0±4.1 years. 69% of CLETs had either one or more adverse events (AEs), or adverse drug reactions (ADRs), within 1 year of surgery, with inflammation being the most common (42%), followed by corneal epithelium defects/disepithelialisation (31%), and blood coagula under the fibrin (24%). One year after surgery, 41% of the 59 primary CLET procedures were successful, 39% partially successful and 20% failed. The most common ADRs recorded for the primary unsuccessful CLETs were ulcerative keratitis, melting/perforation, and epithelial defects/disepithelialisation. Six failed CLETs required reconstructive penetrating keratoplasty (PK). Among CLETs with a favourable outcome, 13 underwent corrective PK (mean 4.8±3.4 years), and thereafter seven eyes maintained integrity of the corneal epithelium, five showed corneal surface failure, and one had recurrent epithelial defects. Corneal graft rejection episodes were reported in 71% and 58% of patients following corrective or reconstructive PK, respectively. Seven primary CLETs with a favourable outcome worsened thereafter, and the overall 3-year long-term effectiveness was 68%. Conclusions: This study addresses important issues regarding possible risks associated with disarray of the ocular surface homeostasis following autologous CLET in patients with limbal stem cell deficiency, despite the fact that the majority of patients experienced a favourable long-term benefit.